2016
DOI: 10.1002/bies.201500187
|View full text |Cite
|
Sign up to set email alerts
|

Formula G1: Cell cycle in the driver's seat of stem cell fate determination

Abstract: Cell cycle dynamics has emerged as a key regulator of stem cell fate decisions. In particular, differentiation decisions are associated with the G1 phase, and recent evidence suggests that self-renewal is actively regulated outside of G1. The mechanisms underlying these phenomena are largely unknown, but direct control of gene regulatory programs by the cell cycle machinery is heavily implicated. A recent study sheds important mechanistic insight by demonstrating that in human embryonic stem cells (hESCs) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…CDK4 and its homolog CDK6 are activated by D-type cyclins in early to mid-G1 phase, whereas CDK2 is activated by E- and A-type cyclins during the late G1 and S phases, respectively [7]. Recent evidence indicates that cell-cycle dynamics have emerged as a key regulator of stem cell fate decisions [810]. Specifically, Cyclin D proteins have been shown to activate CDK4/6, which restricts the activity of Sma- and Mad-related Protein (Smad) 2/3 in late G1 phase and results in a switch from endoderm to neuroectoderm potential in human pluripotent stem cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…CDK4 and its homolog CDK6 are activated by D-type cyclins in early to mid-G1 phase, whereas CDK2 is activated by E- and A-type cyclins during the late G1 and S phases, respectively [7]. Recent evidence indicates that cell-cycle dynamics have emerged as a key regulator of stem cell fate decisions [810]. Specifically, Cyclin D proteins have been shown to activate CDK4/6, which restricts the activity of Sma- and Mad-related Protein (Smad) 2/3 in late G1 phase and results in a switch from endoderm to neuroectoderm potential in human pluripotent stem cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…in daughter cells shortly after NSC mitosis. This is reminiscent of embryonic stem cell differentiation that is also thought to occur in G1 (37,38), especially early G1 at a stage most favorable to massive chromatin remodeling (39). Moreover, we find 25 that this critical period is doubled in human cortical progenitors, which could contribute to their increased self-renewal capacities, thus uncovering a surprising link between mitochondria dynamics and human brain evolution.…”
Section: Main Textmentioning
confidence: 59%
“…Using this approximation, these analyses showed that as developmental time progresses, the proliferation rate of neural progenitors decreases and their cell cycle lengthens (Molina and Pituello, 2017;Kicheva and Briscoe, 2015;Kicheva, et al, 2014). This evolution of the cell cycle length most often associated with differentiation was also observed in various stem cell types (Julian, et al, 2016;Dalton, 2015). suggesting that indeed cell cycle phase durations are stochastic and independent.…”
Section: The Lengthening Of the Cell Cycle Results From Enhanced Hetementioning
confidence: 89%